Three new species of Apiospora (Apiosporaceae, Amphisphaeriales) associated with diseased bamboo in China - Xiaoyun Chang; Yuanyuan Wang; Tao Xu; Guangshuo Li; Xianghua Yue; MingJun Chen (MycoKeys)
Apiospora is widely distributed worldwide, primarily comprising pathogens, endophytes, and saprobes associated with plants, and most of its hosts are Poaceae. In this study, 37 pathogenic strains of Apiospora were isolated from diseased bamboo collected in the provinces of Hunan and Guizhou, China. Multilocus phylogenetic analysis using combined ITS, LSU, TUB2, and TEF1 sequence data, along with morphological assessments, identified three new species: A. bambusiparasitica sp. nov., A. qiannanensis sp. nov., and A. xiangxiense sp. nov. Descriptions, illustrations, and phylogenetic trees for the newly discovered species are provided and compared with closely related Apiospora species to enhance our understanding of the genus Apiospora. The pathogenicity test results demonstrated that the three new species could cause bamboo culm diseases, providing valuable information for the diagnosis and management of bamboo culm diseases.